Inovasi E-Multimedia Interaktif Fisika Berbasis STEM Untuk Meningkatkan Literasi dan Keterampilan Abad 21 - Widya; Zainul Mujtahid; Amam Taufiq Hidayat; Agus Muliaman (Kappa Journal, 2024)
This research aims to develop an Interactive Physics E-Multimedia based on STEM Education to enhance students' scientific literacy and 21st-century skills, including communication, collaboration, critical thinking, and creativity. The study follows a Research and Development (R&D) method with three stages: analysis and exploration, design and construction, as well as evaluation and reflection. The product trials were conducted with 11th-grade students at SMA Negeri 1 Lhokseumawe. The findings reveal that the use of interactive E-multimedia is effective in improving students' understanding, with an average post-test score of 80.4 compared to a pre-test score of only 35.2. Expert validation indicates that the product is suitable for use, with an average score of 85 for content, 82.85 for construction, and 80 for design. The product's practicality was also rated highly by both students and teachers, with an average score of 4.09 out of 5. Additionally, students showed strong interest in the interactive and easily accessible digital learning media. Thus, the STEM-based interactive physics E-multimedia is effective in enhancing scientific literacy and 21st-century skills, making it a valuable tool for supporting self-directed learning